Diseño de infografía ilustrada para el reconocimiento cultural de los personajes tradicionales de la comparsa del Corpus Christi del cantón Pujilí parroquia La Matriz - Arcos Narváez, Jessica Raquel (2017)
In order to contribute to recognize the culture of the Pujilí canton, the design of an illustrated infographic is developed, which includes information synthesized from the feast of Corpus Christi, and which are the characters that make it up. For the execution of the research project were carried out different processes, the search for information that supports the theoretical framework was based on documentary researches, data collection through field research; where the surveys and interviews were used as tools to obtain reliable data of the festival and facility of development of the project, finally the application of the methodology of Bruno Munari for the fulfillment of the proposal. The design of infographics is supported graphically and textually, which is why the statement is based on the execution of sketches, digital illustration of characters, information design and composition of the final work; which is presented in aesthetic and can be implemented in different strategic points that society frequently attends….